2021
DOI: 10.3390/healthcare9010039
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Secondhand Smoke and Stress, Depression, and Suicidal Ideation in Adolescents

Abstract: Background: Secondhand smoke (SHS) is an important risk factor for adolescents’ health. Several studies have reported that SHS is as dangerous as active smoking. Therefore, this study aimed to investigate the association between exposure to SHS and mental health, including stress, depression, and suicidal ideation, in adolescents. Methods: Using raw data from the 2018 14th Korea Youth Risk Behavior Web-Based Survey, we analyzed the effects of sociodemographic characteristics on stress, depression, suicidal ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…It is possible that the absence of an association with CVD observed in the present study reflects a greater robustness to residual confounding, selection bias, and reverse causation. To this extent, our findings may support claims that previous observational estimates of ETS exposure and its attributable risk are overestimated (63,64), However, none of these studies are policy evaluations, and direct comparisons with these previous estimates of the effect of ETS are difficult due to the common practice of treating ETS exposure as a dichotomous variable (9,7577). Moreover, given the difficulty in performing reliable power calculations for multivariable-MR studies, we cannot exclude the possibility of an effect of environmental tobacco smoking on stroke, cardiovascular disease, hypertension, and depression, albeit of a magnitude much smaller than that of first-hand smoking.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is possible that the absence of an association with CVD observed in the present study reflects a greater robustness to residual confounding, selection bias, and reverse causation. To this extent, our findings may support claims that previous observational estimates of ETS exposure and its attributable risk are overestimated (63,64), However, none of these studies are policy evaluations, and direct comparisons with these previous estimates of the effect of ETS are difficult due to the common practice of treating ETS exposure as a dichotomous variable (9,7577). Moreover, given the difficulty in performing reliable power calculations for multivariable-MR studies, we cannot exclude the possibility of an effect of environmental tobacco smoking on stroke, cardiovascular disease, hypertension, and depression, albeit of a magnitude much smaller than that of first-hand smoking.…”
Section: Discussionsupporting
confidence: 76%
“…It is possible that the absence of an association with CVD observed in the present study reflects a greater robustness to residual confounding, selection bias, and reverse causation. To this extent, our findings may support claims that previous observational estimates of ETS exposure and its attributable risk are overestimated (63,64), However, none of these studies are policy evaluations, and direct comparisons with these previous estimates of the effect of ETS are difficult due to the common practice of treating ETS exposure as a dichotomous variable (9,(75)(76)(77).…”
Section: Comparison With Existing Researchsupporting
confidence: 79%
“…In many studies, smoking is high in adolescents with previous depressive symptoms. 13,14 The results of a longitudinal epidemiological study of a population of 10,800 (adolescence to early adulthood) in the USA showed that the link between depressive symptoms and substance abuse was bidirectional. Another study found that higher levels of depression in adolescence were associated with more frequent abuse of psychoactive substances in early adulthood; it emphasized that more frequent substance abuse was also associated with an increase in the intensity of depressive symptoms after a few years.…”
Section: Discussionmentioning
confidence: 99%
“…Even if SHS exposure does not lead to smoking in this age group, it still poses significant health risks; SHS exposure is a preventable risk factor for the development of cardiovascular disease through the development of endothelial dysfunction [22], lung and breast cancer [23], upper and lower respiratory tract infections, asthma [6], and COPD [7]. Additionally, SHS exposure is associated with mental health issues in non-smoking adolescents, including stress, major depressive disorder, generalized anxiety, and attention-deficit/ hyperactivity disorder [24]. Interventions to reduce SHS exposure among adolescents and young adults in Lao PDR are needed to prevent future tobacco use and associated morbidity.…”
Section: Discussionmentioning
confidence: 99%